Extensional Utilitarianism: The Role of Happiness According to J.S. Mill - Mesa Díez, David Santiago (2024)
This paper aims to show that the idea of happiness defended by John Stuart Mill is based on a notion of utility that must be understood in extensional terms. This means that, according to Mill, the idea of happiness does not subordinate other practical precepts—such as the ones of justice and freedom. Instead, these precepts build the set of rules that enable its realization. This approach of Mill, which I call “extensional utilitarianism”, allows me to highlight the fundamental role that happiness plays in the context of Mill’s practical philosophy.